Agitation in cognitive disorders: International Psychogeriatric Association provisional consensus clinical and research definition. (14th October 2014) - Cummings, Jeffrey; Mintzer, Jacobo; Brodaty, Henry; Sano, Mary; Banerjee, Sube; Devanand, D.P.; Gauthier, Serge; Howard, Robert; Lanctôt, Krista; Lyketsos, Constantine G.; Peskind, Elaine; Porsteinsson, Anton P.; et al.
ABSTRACT: Background: Agitation is common across neuropsychiatric disorders and contributes to disability, institutionalization, and diminished quality of life for patients and their caregivers. There is no consensus definition of agitation and no widespread agreement on what elements should be included in the syndrome. The International Psychogeriatric Association formed an Agitation Definition Work Group (ADWG) to develop a provisional consensus definition of agitation in patients with cognitive disorders that can be applied in epidemiologic, non-interventional clinical, pharmacologic, non-pharmacologic interventional, and neurobiological studies. A consensus definition will facilitate communication and cross-study comparison and may have regulatory applications in drug development programs. Methods: The ADWG developed a transparent process using a combination of electronic, face-to-face, and survey-based strategies to develop a consensus based on agreement of a majority of participants. Nine-hundred twenty-eight respondents participated in the different phases of the process. Results: Agitation was defined broadly as: (1) occurring in patients with a cognitive impairment or dementia syndrome; (2) exhibiting behavior consistent with emotional distress; (3) manifesting excessive motor activity, verbal aggression, or physical aggression; and (4) evidencing behaviors that cause excess disability and are not solely attributable to another disorder (psychiatric, medical, or substance-related). A majority of the respondents rated all surveyed elements of the definition as "strongly agree" or "somewhat agree" (68–88% across elements). A majority of the respondents agreed that the definition is appropriate for clinical and research applications. Conclusions: A provisional consensus definition of agitation has been developed. This definition can be used to advance interventional and non-interventional research of agitation in patients with cognitive impairment.